An hydrochemical answer to a legislative demand involving health risk related to water quality - Bonotto, Daniel Marcos [UNESP]; Caprioglio, L. [UNESP] (WITPRESS LTD., 2001)
Effluents and surface waters around an area involved with the inking of tissues at Itatiba municipality, São Paulo State, Brazil, were chemically analyzed with the purpose of evaluating the influence on the water quality of the chemicals released, as well to provide answers to legislative requirements related to the São Paulo State Register 997 published on 31 May 1976.
Keywords: Cost benefit analysis; Drainage; Effluents; Environmental impact; Environmental protection; Health risks; Industrial applications; Laws and legislation; Public policy; Social aspects; Surface waters; Water pollution control; Hydrological resources; Industrial processes; Surface drainage; Water quality